2016
DOI: 10.2147/clep.s114946
|View full text |Cite
|
Sign up to set email alerts
|

Similar long-term survival of consecutive in-hospital and out-of-hospital cardiac arrest patients treated with targeted temperature management

Abstract: ObjectiveThe long-term survival of in-hospital cardiac arrest (IHCA) patients treated with targeted temperature management (TTM) is poorly described. The aim of this study was to compare the outcomes of consecutive IHCA with out-of-hospital cardiac arrest (OHCA) patients treated with TTM.Design, setting, and patientsRetrospectively collected data on all consecutive adult patients treated with TTM at a university tertiary heart center between 2005 and 2011 were analyzed.MeasurementsPrimary endpoints were surviv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 26 publications
2
29
0
Order By: Relevance
“…A possible explanation of this finding could be that OHCA patients primarily die from severe neurological injury leading to WLST, and thereby have affected NPi values, whereas IHCA patients and patients with other diagnoses than cardiac arrest also die from non-neurological complications, for example cardiogenic shock and sepsis not likely to affect the pupillary light reflex. 30,33,34 In accordance with previous studies made in OHCA patients we found that automated pupillometry has a high predictive value, complementing clinical tools such as EEG, SSEPs and neuron-specific enolase. 35,36 One major advantage of pupillometry is the simplicity of the procedure.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…A possible explanation of this finding could be that OHCA patients primarily die from severe neurological injury leading to WLST, and thereby have affected NPi values, whereas IHCA patients and patients with other diagnoses than cardiac arrest also die from non-neurological complications, for example cardiogenic shock and sepsis not likely to affect the pupillary light reflex. 30,33,34 In accordance with previous studies made in OHCA patients we found that automated pupillometry has a high predictive value, complementing clinical tools such as EEG, SSEPs and neuron-specific enolase. 35,36 One major advantage of pupillometry is the simplicity of the procedure.…”
Section: Discussionsupporting
confidence: 89%
“…A possible explanation of this finding could be that OHCA patients primarily die from severe neurological injury leading to WLST, and thereby have affected NPi values, whereas IHCA patients and patients with other diagnoses than cardiac arrest also die from non-neurological complications, for example cardiogenic shock and sepsis not likely to affect the pupillary light reflex. 30,33,34…”
Section: Discussionmentioning
confidence: 99%
“…This 1-year mortality rate was slightly higher in IHCA patients than in OHCA patients. Though in a smaller sample, Engsig et al 25 investigated long-term outcomes and showed comparable 1-year mortality rates, which were similar for IHCA and OHCA patients (47% and 51%, respectively). We found a stable 1-year mortality rate between 2010 and 2016 for IHCA patients.…”
Section: Discussionmentioning
confidence: 98%
“…As stated in the 2015 guidelines, since 2010, a temperature of 32À34 C is recommended, which changed in 2015 to 36 C. 22 Several studies showed different results in goal temperatures for the TTM, but they all recommend using hypothermia or normothermia and preventing hyperthermia. 8,22,35À37 However, Engsig et al 25 showed no difference in IHCA and OHCA patients. Wang et al 38 showed a benefit for TTM in IHCA patients, but TTM was performed in only 3.2% of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study were not considered powerful enough to change the recommendation in guidelines [ 29 ]. On the other hand, when comparing IHCA and OHCA patients treated with TTM, 2 retrospective studies published in 2016 showed no differences in short- and long-term survival rates or neurologic outcomes, indicating the benefits of TTM for both groups might be similar [ 6 , 30 ].…”
Section: Introductionmentioning
confidence: 99%